PERANAN PERPUSTAKAAN DALAM PENGEMBANGAN LITERASI PADA PENGELOLA PERPUSTAKAAN SEKOLAH DI KABUPATEN BULELENG - i wayan mudana (ACARYA PUSTAKA, 2018)
PERANAN PERPUSTAKAAN DALAM PENGEMBANGAN LITERASIPADA PENGELOLA PERPUSTAKAAN SEKOLAH DI KABUPATEN BULELENGOlehI Wayan Mudana, dkk.ABSTRACTThis community work aimed at constructing the role of librarians in developingliteracy in the young generation. This study was done with the elementary school teachersin Buleleng regency by reading two main materials that discuss the role of librarians indeveloping literacy, both in relation to the development of basic reading and writingliteracy and developing data literacy, technology, and humanity literacy. Theimplementation of this community work was done in the form of a constructive lecture anddiscussion.This activity ran well according to the plan and the participants were enthusiasticparticipating in it. The participants said that they were very interested and got a widerinsight about the role of a library in developing literacy. Thus it can be used as a model ofreference in strengthening the role of libraries in developing literacy at their respectiveschool.Keywords: role, library, strengthening, literacy